The specificity of the Threat/Control-Override concept in schizophrenia – new insights from a retrospective cross-sectional study of forensic homicide offenders - Findeis, Hannelore; Strauß, Maria; Kröber, Hans-Ludwig (Frontiers in Psychiatry, 2025)
IntroductionThere is evidence that there is a small group of people with schizophrenia spectrum disorders who are more likely to commit homicide than those in the general population. The aim of this study is to re-examine the much-discussed psychopathological concept of Threat/Control-Override with particular regard to its specificity for schizophrenia spectrum disorders, which has not been investigated to date.MethodsA file-based, retrospective, cross-sectional study was conducted to obtain a complete overview of all forensic homicide offenders detained in the Berlin Forensic Hospital as of 31 December 2014.ResultsOf a total of 614 forensic patients, 110 committed homicide (17.9%). There are three main diagnostic groups in the forensic hospital who committed homicide: schizophrenia spectrum disorders (n=78), substance use disorders (n=11), and personality disorders (n=21). All patients were characterised by being male, unemployed and single. Both the total TCO complex (p=.001) and the Threat (p=.001) and Control-Override (p=.001) symptoms were statistically significantly more frequent in patients with schizophrenia spectrum disorders in the group comparison.DiscussionFor the first time, the TCO complex is examined in a cross-diagnostic comparison, and the specificity of TCO for patients with schizophrenia spectrum disorders with the most serious violent offences can be demonstrated. In order to avoid false positives and to be able to identify clear psychopathological risk symptoms, future studies should include larger samples and, most importantly, non-offending controls.